Candida auris: An Overview of How to Screen, Detect, Test and Control This Emerging Pathogen - Teresa Fasciana; Andrea Cortegiani; Mariachiara Ippolito; Antonino Giarratano; Orazia Di Quattro; Dario Lipari; Domenico Graceffa; Anna Giammanco (MDPI AG, 2020)
The multidrug-resistant yeast Candida auris is associated with invasive infections in critically ill patients and has been isolated in different countries worldwide. Ease of spread, prolonged persistence in the environment and antifungal drug resistance pose a significant concern for the prevention of transmission and management of patients with C. auris infections. Early and correct identification of patients colonized with C. auris is critical in containing its spread. However, this may be complicated by C. auris strains being misidentified as other phylogenetically related pathogens. In this review, we offer a brief overview highlighting some of the critical aspects of sample collection, laboratory culture-dependent and independent identification and the susceptibility profile of C. auris.